PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU DENGAN MODERASI SUPERVISI AKADEMIK Studi pada Guru Kelas SD di UPT Dinas Pendidikan Kecamatan Gunem Kabupaten Rembang - Sutrisno Budi Untara, 1252020054; Liana, Lie (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of this study was to examine the influence of Competence and Motivation on Academic Performance Supervision Master as a moderating variable in the Elementary School Classroom Teachers in the District Education Office Unit Gunem Rembang . The population in this study were all primary school classroom teacher in the District Education Office Unit Gunem Rembang totaled 116 teachers , primary data was collected using a questionnaire instrument to measure variables using Likert scale . Methods of data using multiple regression analysis . Hypothesis test used in this study is the t-test at a significant level (a ) 0.05 . The study of the effect of variable Kompetesnsi , motivation , the performance of teachers who moderated the academic supervision of primary school teachers in the District Education Office Unit Gunem Rembang , it is concluded that : Teacher Competencies no effect on teacher performance , motivation and a significant positive effect on teacher performance . Academic supervision does not affect the performance of teachers . The test results indicate that the interaction : Supervision academic positively and significantly moderate the effect of teacher competence on teacher performance , academic supervision significantly moderate the effects of motivation on teacher performance . Keywords : Competence , Motivation , academic supervision , teacher performance Â